2020
DOI: 10.1136/bmjopen-2020-041750
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ethnic inequalities in mortality related to COVID-19 infections: findings from an ecological analysis of England

Abstract: ObjectivesIn the absence of robust direct data on ethnic inequalities in COVID-19-related mortality in the UK, we examine the relationship between ethnic composition of an area and rate of mortality in the area.DesignEcological analysis of COVID-19-related mortality rates occurring by 24 April 2020 and ethnic composition of the population. Account is taken of age, population density, area deprivation and pollution.SettingLocal authorities in England.ResultsFor every 1% rise in proportion of the population who … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…Ethnic minority. Owing to notable ethnic inequalities in COVID-19 infection and mortality rates and in the cascading socioeconomic impact of the pandemic in the UK [18,19], we use a dummy variable to distinguish between white British/Irish adolescents (¼0; 84%) and ethnic minority adolescents (¼1; 16%). Small cell sizes prevented us from disaggregating ethnic minority adolescents into more detailed subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…Ethnic minority. Owing to notable ethnic inequalities in COVID-19 infection and mortality rates and in the cascading socioeconomic impact of the pandemic in the UK [18,19], we use a dummy variable to distinguish between white British/Irish adolescents (¼0; 84%) and ethnic minority adolescents (¼1; 16%). Small cell sizes prevented us from disaggregating ethnic minority adolescents into more detailed subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…Addressing racial and ethnic discrimination is vital to global efforts in defeating COVID-19 (Bhala et al 2020). Data from the UK, US and Europe find racial and ethnic minority groups have experienced disproportionately high rates of infection and mortality (Bhala et al 2020; Office for National Statistics 2021; Nazroo and Becares 2020;Valeriani et al 2020). Multiple and inter-related proximal causes of such inequalities have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…They are also more likely to be employed as essential workers or less able to work from home, and therefore experience a greater risk of exposure at work or commuting (Office for National Statistics 2021). Underlying these more immediate risk factors is the cumulative impact of structural and institutional racism (Nazroo and Becares 2020).…”
Section: Introductionmentioning
confidence: 99%
“…12 Nazroo et al from United Kingdom reported that rates of COVID-19-related mortality within a local authority increased as the proportion of the population who were of ethnic minority increased. 13 Goodman et al in a cross-sectional United States population demonstrated that men, hypertension and obesity, age 20-39 years were associated with the highest mortality in hospitalized patients. 14 Zhang et al from Wuhan epicenter demonstrated that male sex, a severe COVID-19 condition, expectoration, muscle ache, and decreased albumin were independent risk factors for mortality.…”
Section: Discussionmentioning
confidence: 98%